Effectiveness of Stroke Bundle Care in Emergency Unit on Acute Stroke Patient’s Outcome: Literature Review - Agus Setyo Nugroho; Ni Luh Widani (Media Publikasi Promosi Kesehatan Indonesia (MPPKI), 2024)
Background: Stroke leads to death and disability with continuously increasing incidence rates. Immediate management of acute stroke plays a crucial role in minimizing its impact. Comprehensive management through effective stroke bundle care in emergency units has been recognized as an efficient approach and is a crucial step in determining accurate actions, with the potential to enhance patient independence and reduce morbidity and mortality. Objective: The aim of this theoretical study is to explore the impact of implementing a stroke care bundle in the emergency unit on the outcome of acute stroke patients. Method: This study employs a literature review method with 20 journals from three databases: PubMed, Semantic Scholar, and Google Scholar. Results: Stroke bundle care significantly improves patient outcomes, evident in increased Barthel Index and decreased mortality rates. Clinical factors, particularly NIHSS scores, significantly determine patient outcomes, and attention to nursing, time coordination, and clinical factor management can enhance stroke care effectiveness. Conclusion: This study reaffirms that the implementation of stroke bundle care significantly enhances outcomes for patients with acute stroke by reducing mortality rates, improving independence, and fostering effective coordination among the care team. Recommendation: Further integration of stroke bundle care into clinical practice is needed, with in-depth research on clinical factors and interdisciplinary collaboration to enhance acute stroke management.